Green Procurement and Eco-Design Practices and Their Implications for Operational Performance in Indonesia’s Food Retail Sector - Mulyana Sari; Iskandar Arifin; Andi Nurul Suci Amalia (Fakultas Ekonomi, Universitas Muslim Indonesia, 2026)
This study examines the disclosure maturity of Green Procurement and Eco-Design practices in Indonesia’s food retail sector and their alignment with disclosed patterns of Operational Performance. A descriptive comparative content analysis was conducted using annual and sustainability reports of five leading retailers: Alfamart, Alfamidi, MPPA (Hypermart), MAP Boga Adiperkasa, and Supra Boga Lestari. Fifteen indicators were assessed across three constructs and rated using a five-point disclosure maturity scale capturing the depth and clarity of reported practices. The findings reveal heterogeneous disclosure maturity across firms. Alfamart and Hypermart/MPPA show the highest maturity in Green Procurement and Eco-Design, while MAP Boga Adiperkasa exhibits a more balanced profile across both constructs. Alfamidi reports relatively strong Eco-Design disclosure despite limited Green Procurement maturity, whereas Supra Boga Lestari reflects less structured disclosure across constructs. Operational Performance disclosures vary within a narrower range, indicating that energy- and waste-related themes are commonly reported across firms. Overall, higher maturity in green practice disclosures is associated with more structured operational performance narratives, although gaps remain in process innovation and monitoring-related disclosures. These findings provide insights for retail sustainability governance and reporting practices and offer directions for future research on disclosure-based sustainability assessment in emerging market supply chains.